2019
DOI: 10.2147/jpr.s176889
|View full text |Cite
|
Sign up to set email alerts
|

<p>Gaining insights on the influence of attention, anxiety, and anticipation on pain perception</p>

Abstract: Purpose This article highlights the influence of attention and pain anticipation on pain attenuation. Pain-related trait anxiety was found to moderate the effect that attention strategies impose on pain perception. This article may contribute to clinical treatments quality, where pain attenuation effect is desired. Participants and methods One hundred seven participants, comprising of 72 (67%) females and 35 (33%) males between the age of 17 and 48 (M=22.6, SD =4.36), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…On the other hand, distraction tasks that use the sense of sight show results that mark a tendency in favor of these tasks in both adults and children . We highlight the study by Law et al., in which children with an average age of 8.9 years participated.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…On the other hand, distraction tasks that use the sense of sight show results that mark a tendency in favor of these tasks in both adults and children . We highlight the study by Law et al., in which children with an average age of 8.9 years participated.…”
Section: Discussionmentioning
confidence: 60%
“…The distraction tasks that use the sense of sight had a potentially greater effect than other senses in alleviating pain, since sight is the dominant sense in terms of perception, playing a prominent role in pain perception . Pain reduction with visual distractors in healthy children and adults, with pain induced experimentally, tends to confirm this idea.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The neural activity along the pain transmission pathway is inhibited or amplified by ascending and descending neural circuits (for a revision see Woolf, 2018). This modulation allows a wide range of factors to modulate pain sensation and perception, including psychosocial and environmental factors (for a review see Chayadi and Mcconnell, 2019).…”
Section: Nociceptive Signaling Pathway and Pain Hypersensitivitymentioning
confidence: 99%
“…The results indicated that attention competition was helpful for reducing pain. 13 Changes in cognitive and emotional effects could be reflected by gamma neural oscillations in parietal and occipital regions. 14,15 Studies on pain induced by external stimulation and nociceptive input have found that parietal and occipital regions have specific EEG activity patterns.…”
Section: Introductionmentioning
confidence: 99%